W opozycji do mitu i micie opozycji. Analiza polaryzacji stanowisk i ocen dotyczących Poznańskiego Czerwca '56, czyli rzecz o strajku na tle ekonomiczno-socjalnym i zamieszkach zbrojnych o charakterze politycznym oraz o antykomunistycznym powstaniu... - Kałużna, Joanna (Refleksje. Pismo naukowe studentów i doktorantów WNPiD UAM, 2018)
The article focuses on the question of Poznań 1956 protests. It presents three different types of showing this event and compares them. The article presents how the way of describing this historical event has been changing. Firstly, the author characterizes the statement of the communist authority in 1956, then the elaborations from 1980s (written during the “Carnival of Solidarity”) and finally, two different ways of contemporary analysis of what happened on the 28th of June, 1956. To sum up, the article emphasizes characteristic features of these elaborations which